2020
DOI: 10.1007/s11251-020-09525-2
|View full text |Cite
|
Sign up to set email alerts
|

When failure fails to be productive: probing the effectiveness of productive failure for learning beyond STEM domains

Abstract: The current work builds on research demonstrating the effectiveness of Productive Failure (PF) for learning. While the effectiveness of PF has been demonstrated for STEM learning, it has not yet been investigated whether PF is also beneficial for learning in non-STEM domains. Given this need to test PF for learning in domains other than mathematics or science, and the assumption that features embodied in a PF design are domain-independent, we investigated the effect of PF on learning social science research me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
1
18
1
Order By: Relevance
“…Betz et al, 2016;Lepper, 1988). However, it should be mentioned that PF students in the present study did not outperform DI students on a knowledge test (see our parallel study on the same dataset: Nachtigall et al, 2020). However, the findings of our previous study demonstrated no correlation between students' perceived authenticity and their performance on a knowledge test.…”
Section: Hypothesis 4 (H4)contrasting
confidence: 64%
See 4 more Smart Citations
“…Betz et al, 2016;Lepper, 1988). However, it should be mentioned that PF students in the present study did not outperform DI students on a knowledge test (see our parallel study on the same dataset: Nachtigall et al, 2020). However, the findings of our previous study demonstrated no correlation between students' perceived authenticity and their performance on a knowledge test.…”
Section: Hypothesis 4 (H4)contrasting
confidence: 64%
“…We did not administer a pretest assessing students' knowledge about social science research methods, because such a pretest could have activated relevant prior knowledge in students. Consequently, the beneficial effects hypothesized to underlie the initial problem-solving phase of PF could have been negated (see Newman & DeCaro, 2018; see also Nachtigall et al, 2020). However, the design of the present study partly built on the assumption that secondary school students lack knowledge about social science research methods and, thus, are unable to accurately judge the authenticity of learning activities that try to emulate processes of scientific inquiry within the social sciences.…”
Section: Limitationsmentioning
confidence: 94%
See 3 more Smart Citations